2016
DOI: 10.1002/ejoc.201600432
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Cascade Reaction of α‐Cyano Ketones and Isatylidene Malononitriles: Asymmetric Construction of Spiro[4H‐pyran‐oxindoles]

Abstract: α‐Cyano ketones have been employed for the first time as Michael donors in the construction of chiral spiro compounds. By using only 2 mol‐% of a chiral multifunctional organocatalyst, chiral spiro[4H‐pyran‐oxindole] derivatives were prepared in yields of 97–99 % with enantioselectivities of 76–97 % ee. This method provides a new approach to the synthesis of chiral spirocyclic oxindoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…(Figure 35). [66] In this case the cascade cyclisation took place to form the heterocyclic product in remarkably high ees. The initial screening with the N-benzylated malononitrile gave a product of 72% but then switching to the N-methylated derivative with the addition of 1 mol% of morpholine at lower temperature raised the ee to 90%.…”
Section: Use Of N-thiourea Tsdpen Derivatives In Asymmetric Catalysismentioning
confidence: 97%
“…(Figure 35). [66] In this case the cascade cyclisation took place to form the heterocyclic product in remarkably high ees. The initial screening with the N-benzylated malononitrile gave a product of 72% but then switching to the N-methylated derivative with the addition of 1 mol% of morpholine at lower temperature raised the ee to 90%.…”
Section: Use Of N-thiourea Tsdpen Derivatives In Asymmetric Catalysismentioning
confidence: 97%
“…Wu and co‐workers devised an enantioselective domino Michael/cyclization reaction between isatylidenemalononitriles 615 and α‐cyano ketones 139 for the synthesis of spiro[4 H ‐pyran‐oxindole] derivatives 635 . Quinidine‐derived thiourea catalyst 636 provided good to excellent ee values for the desired products (Scheme ) . It was found that both the hydrogen bonding moiety and the tertiary amine moiety of the catalyst were required for achieving such good results.…”
Section: Multifunctional Catalystsmentioning
confidence: 99%
“…It was found that both the hydrogen bonding moiety and the tertiary amine moiety of the catalyst were required for achieving such good results. For example, with catalyst 637 , which is lacking the tertiary amine moiety in its structure, only a racemic product was obtained …”
Section: Multifunctional Catalystsmentioning
confidence: 99%
“…The synthesis of several spiro[4 H -pyran-oxindole] derivatives 26 was proposed by Wu and co-workers by using α-cyano ketones 25 as nucleophiles ( Scheme 6 ) [ 31 ]. In the presence of very low loadings of quinidine-derived thiourea organocatalyst XVII (2 mol %) and morpholine (1 mol %) in dichloromethane at 0 or −10 °C, the cascade process takes place within less than two hours and accommodates a broad range of substrates affording the expected products in excellent yields and high enantioselectivities.…”
Section: Thiourea-based Catalystsmentioning
confidence: 99%